YOU and YOUR CREDIT: Credit Reports - Michael S. Gutter; Joan P. Elmore; Travis P. Mountain (EDIS)
This document is FCS7232, part of the YOU and YOUR CREDIT series by Michael S. Gutter, Joan P. Elmore, and Travis P. Mountain. Published by the UF Department of Family Youth and Community Sciences, September 2008.